Novel MRI hyper‐realistic head‐up display system for patient comfort. Issue 11 (11th October 2018) - Sasaki, Takashi; Hotta, Aira; Murata, Takahiro; Ueda, Yu; Okumura, Haruhiko
Abstract: Virtual reality technologies are significant for medical applications. Canon's magnetic resonance imaging (MRI) system, "Vantage Galan 3T, " focused on patient comfort. The MRI head‐up display (MRI‐HUD) system was also provided as "MR Theater" for this purpose. MRI‐HUD is based on Head Dome Projector (HDP). HDP is a head‐mounted display consisting of a dome‐shaped screen and a mobile LED projector with an ultra‐wide projection lens. HDP was created to demonstrate that non‐flat plane images provide a superior hyper‐realistic impression. In the development process of HDP, we carried out subjective evaluation to confirm the effects of elimination of the flat plane for a hyper‐realistic impression. And we confirmed that the images on the dome screen provide a better impression than the images on a cylindrical screen or a flat screen. MRI‐HUD is a head‐up display system that uses HDP as a real image source. A dome screen and a reflection mirror composed of non‐magnetic materials are constructed beside the patient's bed in the MRI gantry. MRI‐HUD creates wide field‐of‐view images that eliminate the feeling of limited space of the MRI gantry from the beginning to end of the examination. Abstract : Head‐up display for magnetic resonance imaging (MRI‐HUD) system uses dome screen as a real image source. A dome screen and a reflection mirror composed of non‐magnetic materials are constructed beside the patient's bed in the MRI gantry. MRI‐HUD creates wide‐field‐of‐view images that eliminate the feeling of limited space of the MRI gantry from the beginning to the end of the examination.